(untitled) (Palíndromo, 2025)
The text presents reflections based on the book “Resonances: vibrations by sympathy and frequencies of insurgencies”, published by Editora UFRJ in 2021. It should be noted that resonance or vibration by sympathy is initially an acoustic phenomenon in which bodies spontaneously vibrate based on their affinity with the frequencies of other bodies. However, the manifestations of this relational mode transcend acoustics, indicating true machineries for the creation (and destruction) of worlds, whether objective, such as the forms in the observable universe, or subjective, made up of frequencies of affection placed in a responsive relationship. To enter into resonance is to allow oneself to be caught up in the identification that the frequency of an external body corresponds to one’s own, present in latency. If resonance can disintegrate bridges or lead crystal bowls to catastrophe, a swarm of resonant practices can reach sufficient power to collapse other structures as well.